The Use of Taguchi Method in Design of Dies Propeller Production Using CNC Machine - Edi Jadmiko; Purwadi Wahyunugroho (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2020)
Propeller is a rounded blade that rotates in a circle, helping to move a vehicle by pushing against water or air. A speed boat's propeller moves it forward by spinning against the water. Propellers use the laws of physics to propel, or drive forward, an aircraft or a boat. The basic structure of a propeller is a spinning or rotating the shaft with wide, curved blades attached to it. The very simplest propellers were first used in ancient Greece, where the inventor Archimedes invented a